Coal Worker's Pneumoconiosis Mimicking Lung Cancer in a 75‐Year‐Old Woman With a History of Breast Cancer: A Clinical Case Report - Yeganeh Pakbaz; Farzan Moodi (Clinical Case Reports)
ABSTRACT Pneumoconiosis, caused by inhaling mineral dust, remains a significant occupational disease, despite a declining incidence. Coal workers' pneumoconiosis (CWP), a common subtype, varies in presentation from simple to complicated forms. Differential diagnosis is crucial, especially when CWP manifests as lung masses mimicking malignancy. We present a case of CWP in a 75‐year‐old female with a history of breast cancer, initially suspected of lung cancer due to an incidental mass on chest radiography. Clinical examination, laboratory tests, chest tomography, and biopsy were conducted. The patient, with a history of biomass fuel exposure, presented with a left upper lung mass, initially thought to be lung cancer. Biopsy‐induced hemopneumothorax led to intensive care admission. Histopathology confirmed CWP and conservative management resulted in recovery. Imaging revealed a solid mass in the left upper lung with lymphadenopathy. Histopathology showed carbon‐laden macrophages and anthracosis, consistent with CWP. Imaging modalities, including MRI and FDG‐PET/CT, aid in differentiating CWP from cancer. CWP, mimicking lung cancer, underscores the importance of accurate diagnosis. Imaging features, including nodules with calcifications, guide diagnosis. MRI and FDG‐PET/CT offer valuable insights, albeit with limitations, emphasizing the need for judicious use based on clinical suspicion.